3D CHARTS - TAXONOMY AND IMPLEMENTATION IN A VIRTUAL GLOBE - Schnürer, Raimund; Eichenberger, Remo; Sieber, René; Hurni, Lorenz (Revista Brasileira de Cartografia, 2015)
Charts are key elements in thematic cartography to visualize multivariate data. While taxonomies and construction theories of 2D charts are well-elaborated, a concise framework for classifying and creating 3D charts is still missing. In this paper, we therefore propose a taxonomy for 3D charts which distinguishes between 3D point, line, surface, and solid charts. Special focus is put on the properties of solid charts. Based on these properties and with the aid of open-source software, we create six solid chart maps in a virtual globe which depict spatio-temporal data of the Atlas of Switzerland.